Iron Profile and Status of Anemia with the Associated Factors in Chronic Kidney Disease Patients - Shreewastav, Rupesh Kumar; Joshi, Bishal Raj; Yadav, Rahul; Katwal, Anup; Shrestha, Shailendra (Journal of Nepal Health Research Council, 2023)
Background: One of the main complications of chronic kidney disease is anemia. Disorders of iron homeostasis seen in such patients make the management of anemia more challenging and risky. To obtain the desired result, erythropoietin and iron dose must be carefully regulated. The aim of the study is to find out the prevalence of anemia and level iron indices in patients of chronic kidney disease at a tertiary care hospital. Methods: A cross-sectional descriptive study was conducted on chronic kidney disease patients at a tertiary care center. Demographic data like age, sex, height and weight were collected with the help of using Performa. The hematological and biochemical study variables were assayed by blood sample of the patients in the clinical laboratory services. Data were analyzed by statistical package for the social sciences Version 20.0Results: Out of 171 patients with chronic kidney disease, 162 (94.7%) were anemic, with the highest percentage 54 (31.5%) having hypertension. The median value with inter-quartile range of hemoglobin, serum iron, serum ferritin, TIBC and transferring saturation were 8.9 gm/dl (6.7-10.0), 115.0 (µg/dl) (60.0-140.0), 599.0 ng/ml (142.6-973.0), 279.0 µg/dl (250.0-342.0) and 41.0 % (22.0-53.0) respectively. Serum creatinine and eGFR were significantly correlated with hemoglobin and iron indices.Conclusions: The current study showed that anemia was more prevalent in patients of chronic kidney disease in our setting as compared to similar studies. Hypertension was the most common disease among them. The median value of parameters of iron profile except ferritin among them was within the reference limit.Keywords: Anemia; chronic kidney disease; iron